1035 The International Registry for Niemann-Pick Disease Type C (NP-C) in Clinical Practice. (October 2012) - Wijburg, FA; Mengel, E; Patterson, MC; Wraith, JE; Vanier, MT; Schwierin, B; Muller, A; Drevon, H; Pineda, M
Abstract : Background and Aim: An international disease registry was started in September 2009 to evaluate the long-term disease course of NP-C in clinical settings. Methods: Descriptive data from enrolment are presented for all patients with available data who were included in the Registry as of 19 th August 2011. Results: 121 patients have been enrolled. The median (range) age at enrolment was 16.9 (0.9−56.6) years, age at onset of neurological manifestations was 8.2 (< 1−48.0) years (n=100), and age at diagnosis was 11.8 (0.1−53.9) years (n=110). A history of neonatal jaundice was recorded in 4/4 evaluable patients with early-infantile (EI) onset of neurological manifestations (at age < 2 years; n=9), 6/21 (29%) with late-infantile (LI) onset (at 2 to < 6 years; n=31), 6/21 (29%) with juvenile (JUV) onset (at 6 to < 15 years; n=31), and 3/20 (15%) with adolescent/adult (AA) onset (at ≥ 15 years; n=29). Miglustat therapy at enrolment was recorded in 88/121 (73%) patients; mean (SD) exposure 1.69 (1.85) years (n=86). Neurological manifestations were observed in 71/84 (85%) patients: ataxia (71%), vertical gaze palsy (68%) and dysarthria (62%) were most frequent. Median (range) disability scores (0=normal; 1=worst) were: 0.0 (0.0–0.94) in EI (n=7), 0.29 (0.0–1.0) in LI (n=28), 0.41 (0.15–0.88) in JUV (n=28), and 0.29 (0.06–0.81) in AA-onset patients (n=26). A low proportion of patients had normal language, manipulation, ambulation, and/or swallowing. Conclusions: Over two-thirds of this NP-C cohort had infantile or juvenile onset of neurological manifestations; neonatal jaundice was observed more frequently in these patients versus adolescent/adult-onset patients.